2019
DOI: 10.1002/aic.16581
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerate breakage and adhesion upon impact with complex‐shaped particles

Abstract: Understanding the breakage and adhesion of an agglomerate upon collision with a target particle is a primary step to fathom the adhesive mixing process. While the effect of several variables, such as collision velocity and particle interface energy, on collision behavior has been explored, the effects of target particle morphology have yet to be revealed. In this work, we generate three-dimensional particles with controllable shape and texture using Fourier harmonics and, using the discrete element method, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…These interparticle impacts lead to breakage and redistribution of the particles, which eventually leads to the formation of a spherical shape. 58 On the other hand, it has also been experimentally observed that altering the source of carbonate anions from NH 4 HCO 3 to NaHCO 3 results in transition from cubic to spherical shaped particles. 23 It should be noted that ammonia (NH 3 ) dissolved in the reaction solution acts as a chelating agent and increases the solubility of the transition metal salt through the formation of a metal-ammonia complex ([Mn(NH 3 ) n 2+ ]).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interparticle impacts lead to breakage and redistribution of the particles, which eventually leads to the formation of a spherical shape. 58 On the other hand, it has also been experimentally observed that altering the source of carbonate anions from NH 4 HCO 3 to NaHCO 3 results in transition from cubic to spherical shaped particles. 23 It should be noted that ammonia (NH 3 ) dissolved in the reaction solution acts as a chelating agent and increases the solubility of the transition metal salt through the formation of a metal-ammonia complex ([Mn(NH 3 ) n 2+ ]).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, at higher stirring speeds of 4800 rpm, the moving particles experience a larger Reynolds number, which leads to collision between individual particles preventing their unobstructed growth. These interparticle impacts lead to breakage and redistribution of the particles, which eventually leads to the formation of a spherical shape …”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the shape approximation of the multisphere model is improved by increasing the resolution of surface discretization as well as introducing more spheres, each with a small radius. Complex‐shaped particles have been created with this method in earlier works by the authors, wherein the effect of the target particle shape on the breakage and adhesion pattern of a colliding agglomerate was investigated 34 …”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Source: Reprinted with permission from Elsevier particles have been created with this method in earlier works by the authors, wherein the effect of the target particle shape on the breakage and adhesion pattern of a colliding agglomerate was investigated. 34 3 | SIMULATION SETUP…”
Section: Computational Frameworkmentioning
confidence: 99%
“…The geometric attributes of carrier particles and their influence on dispersion performance are argued to be one of the aspects of DPIs that have been poorly understood . It is well recognized through several in vitro aerosolization tests on carrier‐based DPI formulations with carriers of different size, shape, and roughness, that the carrier morphology imposes a profound and yet inconsistent effect on dispersion .…”
Section: Introductionmentioning
confidence: 99%